Individual Expectations, Limited Rationality and Aggregate Outcomes - Te Bao; Cars Hommes; Joep Sonnemans; Jan Tuinstra (Tinbergen Institute, 2012)
Recent studies suggest that the type of strategic environment or expectation feedback can have a large impact on whether the market can learn the rational fundamental price. We present an experiment where the fundamental price experiences large unexpected shocks. Markets with negative expectation feedback (strategic substitutes) quickly converge to the new fundamental, while markets with positive expectation feedback (strategic complements) do not converge, but show under-reaction in the short run and over-reaction in the long run. A simple evolutionary selection model of individual learning explains these differences in aggregate outcomes.
Keywords: C92; G14; D84; D83; E37; 330; Expectation feedback; under- and overreaction; strategic substitutes and strategic complements; heuristic switching model; experimental economics